Growth in narrative retelling and inference abilities and relations with reading comprehension in children and adolescents with autism spectrum disorder. (November 2020) - McIntyre, Nancy S; Grimm, Ryan P; Solari, Emily J; Zajic, Matthew C; Mundy, Peter C
Background and aims: Extant research indicates that children and adolescents with autism spectrum disorder (ASD) without an intellectual disability (ID) often experience difficulty comprehending written texts that is unexpected in comparison with their cognitive abilities. This study investigated the development of two key skills, narrative and inference abilities, that support higher level text comprehension and their relation to lexical-semantic knowledge, ASD symptomatology, and age. Three questions were addressed: 1.) What was the nature of narrative and inference skill development over time? 2.) What was the relation between narrative or inference development and lexical-semantic knowledge, ASD symptomatology, and age? 3.) Did initial narrative and inferencing skills, and the development of these skills, predict reading comprehension outcomes? Methods: Data from 81 children and adolescents with ASD without ID (FIQ ≥ 75) between the ages of 8-16-years-old at timepoint 1 were collected at 15-month intervals across three timepoints. ASD symptomatology was assessed with the ADOS-2. Standardized narrative retelling, inference, reading comprehension, lexical-semantic knowledge and cognitive assessments were administered. Latent growth curve models were conducted to examine narrative and inference skill development, and conditional growth models were fit to examine the relation between growth trajectories and covariates (lexical-semantic knowledge, ASD symptomatology, age) as well as with the reading comprehension distal outcome. Results: Narrative retelling skills followed a linear trajectory of growth and were a relative strength in this sample, while inference skills were well below average and declined over time relative to age-normed standard scores. Lexical-semantic knowledge explained significant heterogeneity in initial narrative and inference skills, whereas ASD symptomatology was only related to initial narrative retelling abilities and age was only related to initial inference abilities. Timepoint 3 reading comprehension skill (in the below average range) was significantly explained by initial narrative retelling and inference abilities. Conclusions: The results of this study indicate that narrative retelling and inference skills are important for successful reading comprehension for individuals with ASD without ID and that lexical-semantic knowledge underpins these skills. Furthermore, the observation that ASD symptom severity was associated with narrative retelling skills is consistent with the hypothesis that problems in narrative reading skills are associated with the autism phenotype. Finally, inference skill was a particular challenge for individuals in this sample, although age was positively associated with better performance on the assessment. Implications: These findings suggest that narrative and inference skills, in addition to lexical-semantic knowledge, are important to target beginning in elementary grades to improve reading comprehension outcomes for children and adolescents with ASD without ID.